Innovations in Gerontology Education. (17th December 2021) - McDonald, Kimberly; Ellis, Jennifer
Abstract: This session examines innovative approaches to effectively address the aging services workforce needs in rural, Midwestern settings. Presenters will explore career pathways and transfer opportunities in gerontology education, as well as best practices for addressing the educational, professional and personal needs of diverse student populations.